(untitled) (Società e diritti, 2019)
Abstract The relation between force and law is very complicated one. However, if we want to understand what a rule is, what it can do, and how it does, we have to recognize the relevance of the coercive dimension; this is not a necessary character of every rule, but remains the most typical reason that explains why people accord their behaviors to the prescriptions of the rules. Dealing with force, in any case, is not an easy matter: the semantic field to which the term force belongs is very huge and with it we can cover a lot of different situations. For that reason, when we put together law and force, we immediately need to find a third element through which this relationship could be regulated. The force of law leads us to recognize that the acts of force we can accept are the ones that have been defined by the legitimate principle. The coercive dimension is comprehensible just for its legitimacy, and that implies an idea of justice. The Author would like to stress her lecture of Schauer’s reflection on the force of law, is that according to the position that recognise of a force in the very core of law, we are immediately obliged to give to this force a plan in which it can assume a legal meaning, and that is to say, the uncertain ground of the metaphysical, transcendental idea of justice. Key words: Legal positivism, Justice, coercion Riassunto La relazione tra forza e diritto è molto complessa. Tuttavia, se vogliamo capire che cosa sia una norma giuridica, che cosa possa fare, e come lo faccia, dobbiamo riconoscere l’importanza della dimensione coercitiva; questo non è un carattere necessario di ogni norma, ma resta la ragione più tipica che spiega perché le persone accordano i loro comportamenti alle prescrizioni del diritto. Maneggiare il concetto di “forza”, in ogni caso, non è cosa semplice: il campo semantico del termine ‘forza’ è molto grande e si riferisce ad un ampio numero di situazioni diverse. Per questo motivo, quando accomuniamo la “legge” e la “forza”, abbiamo immediatamente bisogno di trovare un terzo elemento attraverso il quale questo rapporto possa essere regolamentato. La dimensione coercitiva è comprensibile solo alla luce del concetto di legittimità e implica un’idea di giustizia. La forza della Legge ci porta a riconoscere che gli atti di forza che possiamo accettare sono solo quelli che siano coperti dal principio di legittimità. L’autrice tiene a sottolineare che la sua interpretazione della saggio di Schauer sulla “forza di legge”, è nel senso che qualora si attribuisca la forza al nucleo centrale del concetto stesso di Diritto, saremmo immediatamente obbligati a collocare questa forza su un piano in cui si può assumere un significato giuridico, vale a dire il terreno incerto dell’idea metafisica e trascendentale della giustizia. Parole chiave: positivismo giuridico, giustizia, coercizione